A new basal iguanodontian (Dinosauria, Ornithischia) from the Upper Cretaceous of Patagonia (Ameghiniana, 2013)
Abstract. We report the discovery of an almost complete skeleton of a new iguanodontian dinosaur, Talenkauen santacrucensis n. gen. et sp., from Maastrichtiano rocks of southwestern Patagonia. Talenkauen is odd in the presence of plate-like structures on both sides of the thorax, which are better interpreted as uncinate processes than dermal armor. Talenkauen and the also Maastrichtian Thescelosaurus neglectus Gilmore from North America, represent the only two ornithischians in which this peculiar feature is currently known. Some derived features unite Talenkauen with other Gondwanan ornithopods, but all the evidence does not offer enough support for an iguanodontian clade endemic from the Southern Hemisphere. Small- to medium-sized ornithischians appear to have been the dominant plant-eating dinosaurs in Antarctica and Australia during the Cretaceous, in contrast with the outstanding abundance of medium sized to giant sauropods in central Gondwana (e.g., South America, Africa, India).Resumen. UN NUEVO IGUANODONTE BASAL (DINOSAURIA, ORNITHISCHIA) DEL CRETÁCICO SUPERIOR DE LA PATAGONIA. Se reporta el descubrimiento de un esqueleto casi completo de un nuevo dinosaurio iguanodonte, Talenkauen santacrucensis n. gen. et sp., de rocas de edad Maastrichtiano del sudoeste de Patagonia. Talenkauen posee placas en ambos lados del tórax, las cuales son interpretadas como procesos uncinados en lugar de armadura dérmica. Talenkauen y Thescelosaurus neglectus (Maastrichtiano, América del Norte), son los únicos dos ornitisquios en los que se conoce esta peculiar característica. Algunos caracteres derivados unen a Talenkauen con otros ornitópodos gondwánicos, pero el conjunto de la evidencia disponible no ofrece sustento suficiente para reconocer un clado de iguanodontes endémico del Hemisferio Sur. Los ornitisquios de pequeño y mediano tamaño parecen haber sido los dinosaurios herbívoros dominantes en Antártida y Australia durante el Cretácico, contrastando con la gran abundancia de saurópodos de mediano a gran tamaño registrada en Gondwana central (p. ej., América del Sur, África, India).